Comparative study of the lived experiences of Canadian-born and foreign-born Chinese Canadian students in Northern Ontario - Wang, Fei (My University, 2006)
Social and cultural adaptation may be issues of importance to students of Chinese origin in Canada, where both Canadian-born and foreign-born Chinese students often experience many problems of adjustment, including the challenge of cultural difference to a new social context. The purpose of this phenomenological study was to provide an in-depth description of the key factors that contribute to differences in the social experiences of Canadian-born and foreign-born Chinese students, and to disseminate results that could be used by policy makers to enable them to better understand and address the needs, interests, and aspirations of students of Chinese origin in Canada. This study employed a qualitative methodology to uncover and describe the internal meaning of the participants’ lived experiences. This study occurred in a North-western Ontario urban community with a Chinese Canadian population of approximately 300. Three Canadian-born and three foreign-born Chinese students were interviewed in this study. Semi-structured interviews with open-ended questions were adopted in this study to allow the participants to express their views on their lives in Northern Ontario, Canada. Four themes emerged: (a) perceptions of ethnic identity; (b) cultural integration; (c) perceptions of academic performance and (d) the effect of Canadian education on career options. The findings of this study indicated that Canadian-born Chinese students differed from their foreign-born counterparts in the following areas: their viewpoints on ethnic identity; their perceptions concerning acculturation; and academic performance. However, both groups of students also shared similarities in their views about Canadian and Chinese educational systems, teaching styles, as well as their career expectations.
Keywords: Chinese students (Ontario, Northern); Chinese Canadians (Ontario, Northern); Chinese Canadian students (Ontario, Northern); Ethnic identity, language and acculturation